Improving Posture Accuracy of Non-Holonomic Mobile Robot System with Variable Universe of Discourse - Siti Nurmaini; Bambang Tutuko; Kemala Dewi; Velia Yuliza; Tresna Dewi (Universitas Ahmad Dahlan, 2017)
This paper presents a method to decrease imprecision and inaccuracy that have the tendency to influence the posture of non-holonomic mobile by using the adaptive tuning of universe of discourse. As such, the primary objective of the study is to force the posture error of x(t), y(t) and θ(t) towards zero. Hence, for each step of tuning the fuzzy domain, about 20% of imprecision and inaccuracy had been added automatically into the variable universe fuzzy, while the control input was bound via scaling gain. Furthermore, the experimental results showed that the tuning of universe fuzzy parameters could increase the performance of the system from the aspects of response time and error for steady state through better control of inaccuracy. Besides, the domains of universe fuzzy input [-4,4] and output [0,6] exhibited good performance in inching towards zero values as the steady state error was about 1% for x(t) position, 0.02% for y(t) position, and 0.16% for θ(t) orientation, whereas the posture error in the given reference was about 0.0002%.